Impact of proposed U.S. tariffs on agricultural trade flows in the Western Hemisphere - Glauber, Joseph W.; Piñeiro, Valeria; Gianatiempo, Juan Pablo (International Food Policy Research Institute, 2025)
In a previous post, we examined how the tariffs could potentially impact countries in Latin America and the Caribbean (LAC) based on current agricultural trade patterns between the United States and its neighbors in the hemisphere. Here, we extend that analysis, examining how tariffs on imports to the U.S. from Canada and Mexico could affect intra-regional trade between the three countries and across Central and South America and the Caribbean.